Couples’ Urinary Bisphenol A and Phthalate Metabolite Concentrations and the Secondary Sex Ratio - Bae, Jisuk (Environ Res, 2015)
With limited research focusing on non-persistent chemicals as exogenous factors affecting human sex selection, this study aimed to evaluate the association of urinary bisphenol A (BPA) and phthalate metabolite concentrations with the secondary sex ratio (SSR), defined as the ratio of male to female live births. The current analysis is limited to singleton live births (n=220, 43.9%) from the Longitudinal Investigation of Fertility and the Environment (LIFE) Study, which enrolled couples upon discontinuing contraception and followed while trying for pregnancy and through delivery those achieving pregnancy. Using modified Poisson regression models accounting for potential confounders, we estimated the relative risks (RRs) of a male birth per standard deviation change in the log-transformed maternal, paternal, and couple urinary BPA and 14 phthalate metabolite concentrations (ng/mL) measured upon enrollment. When maternal and paternal chemical concentrations were modeled jointly, paternal BPA (RR, 0.77; 95% confidence interval [CI], 0.62–0.95) and mono-isobutyl phthalate (RR, 0.82; 95% CI, 0.67–1.00) were significantly associated with a female excess. Contrarily, maternal BPA (RR, 1.16; 95% CI, 1.03–1.31), mono-isobutyl phthalate (RR, 1.28; 95% CI, 1.06–1.54), mono-benzyl phthalate (RR, 1.31; 95% CI, 1.08–1.58), and mono-n-butyl phthalate (RR, 1.24; 95% CI, 1.01–1.51) were significantly associated with a male excess. These findings underscore varying patterns for the SSR in relation to parental exposures. Given the absence of previous investigation, these partner-specific associations of non-persistent chemicals with the SSR need future corroboration.